Reconstructing Professional Legal Ethics within the Framework of Fiqh Qadha and Qur'an: A Normative Study of Islamic Judicial Integrity - Rahmat Sholihin; Adwin Tista; Saila Salsabila (Syariah: Jurnal Hukum dan Pemikiran, 2026)
The modern judiciary faces an unprecedented crisis of legitimacy, marked by widespread ethical violations, corruption allegations, and declining public trust in judicial institutions across Muslim-majority nations. This phenomenon represents a critical juncture requiring the reconstruction of professional legal ethics grounded in Islamic normative sources, particularly Fiqh Qadha and Qur'anic principles that articulate transcendent standards of judicial integrity. The theoretical landscape reveals a significant disjuncture between contemporary positive law frameworks and the rich Islamic jurisprudential heritage addressing judicial ethics. Existing scholarship has predominantly examined either the procedural dimensions of Islamic courts or institutional reforms in secular-positivist contexts, leaving unexamined the substantive ethical reconstruction of the judicial profession itself through integrated Qur'anic and Fiqh Qadha principles. This study aims to systematically reconstruct professional legal ethics within the framework of Fiqh Qadha and Qur'anic principles to establish normative standards for Islamic judicial integrity, examining how classical jurisprudential categories and Qur'anic ethical directives can inform contemporary judicial reform in Muslim societies. Through this reconstruction, the research seeks to create a comprehensive ethical paradigm that simultaneously honors Islamic legal tradition and addresses modern governance challenges. Employing a normative juridical method grounded in library research, the study engages primary sources including the Qur'an, classical fiqh works, contemporary fatwas, and statutory instruments to conduct a qualitative analysis of judicial ethics principles. The research synthesizes textual hermeneutics with jurisprudential comparison to identify core ethical standards applicable to contemporary judicial practice. The findings establish that Islamic normative sources articulate a comprehensive ethical framework centered on justice (al-adl), trustworthiness (amanah), intellectual integrity (fathanah), and moral steadfastness (istiqamah), principles that fundamentally exceed the procedural minimalism of many positive law codes. These principles function not merely as behavioral guidelines but as transcendent standards grounding judicial authority in divine accountability, thereby creating a distinctive ethical architecture superior to purely secular frameworks. The study concludes that reconstructing professional legal ethics through Fiqh Qadha and Qur'anic integration offers a transformative pathway for restoring judicial credibility, strengthening institutional legitimacy, and fostering ethical accountability in Muslim-majority legal systems. The research recommends systematic institutional reform integrating Islamic ethical training, establishing shari'ah-based ethics commissions, and implementing maqasid-aligned oversight mechanisms to operationalize these normative principles in contemporary judicial governance.